The simple art of voting the cognitive shortcuts of Italian voters - Baldassarri, Delia (New York ; Oxford : Oxford University Press, 2013)
In this work, Delia Baldassarri provides a new understanding of how voting works by focusing on how choices are made rather than on what their outcomes are. Drawing on recent advances in cognitive psychology, political cognition, and behavioral economics, Baldassarri distinguishes voters based on the cognitive shortcuts, or heuristics, they use to reduce the complexity of political choice.
Translated from the Italian.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on Oct. 31, 2012).
Keywords: Voting -- Italy; Elections -- Italy; Italy -- Politics and government -- 1994-